On Holding Gains and Losses and the Evaluation of Management: A Reply. - Petri, Enrico (The Accounting Review, 1974)
This article presents a response to a comment on holding gains and losses in accounting in the U.S. The reply has a threefold purpose: to clarify the writer's position in the original paper, to question an implication of the two general propositions and to question whether it succeeded in accomplishing the full intent of the second purpose stated in the note. The conclusion of the discussion is the reaffirmation of the writer's position that existing techniques for measuring and reporting holding activity possesses little or no informal content.